Consensus clinical practice guidelines for the diagnosis and treatment of restless legs syndrome/Willis-Ekbom disease during pregnancy and lactation. (August 2015) - Picchietti, Daniel L.; Hensley, Jennifer G.; Bainbridge, Jacquelyn L.; Lee, Kathryn A.; Manconi, Mauro; McGregor, James A.; Silver, Robert M.; Trenkwalder, Claudia; Walters, Arthur S.; ,
Summary: Restless legs syndrome (RLS)/Willis-Ekbom disease (WED) is common during pregnancy, affecting approximately one in five pregnant women in Western countries. Many report moderate or severe symptoms and negative impact on sleep. There is very little information in the medical literature for practitioners on the management of this condition during pregnancy. Accordingly, a task force was chosen by the International RLS Study Group (IRLSSG) to develop guidelines for the diagnosis and treatment of RLS/WED during pregnancy and lactation. A committee of nine experts in RLS/WED and/or obstetrics developed a set of 12 consensus questions, conducted a literature search, and extensively discussed potential guidelines. Recommendations were approved by the IRLSSG executive committee, reviewed by IRLSSG membership, and approved by the WED Foundation Medical Advisory Board. These guidelines address diagnosis, differential diagnosis, clinical course, and severity assessment of RLS/WED during pregnancy and lactation. Nonpharmacologic approaches, including reassurance, exercise and avoidance of exacerbating factors, are outlined. A rationale for iron supplementation is presented. Medications for RLS/WED are risk/benefit rated for use during pregnancy and lactation. A few are rated "may be considered" when RLS/WED is refractory to more conservative approaches. An algorithm summarizes the recommendations. These guidelines are intended to improve clinical practice and promote further research.